Sejarah Hukum Perkawinan di Dunia Islam - Umar Umar; Faisar Ananda Arfa; Irwansyah Irwansyah (Student Research Journal, 2025)
This study examines the historical evolution of marriage laws in Islam, from the early Islamic period to their development in modern Muslim-majority countries. It reveals significant changes in marriage regulations influenced by the social, political, and cultural contexts of various eras. The research highlights that early Islamic marriage laws emphasized justice and the protection of women's rights. However, over time, diverse interpretations emerged, particularly in traditional and modern Islamic nations. The study further explores the role of Islamic scholars and legal institutions in adapting marriage laws based on Quranic verses and Hadith and how these laws ha The study addresses contemporary issues such as polygamy, women's rights in marriage, and the registration of marriages in Muslim-majority countries, reflecting ongoing challenges in applying Islamic marriage laws. The research aims to trace the historical development of Islamic marriage laws and analyze how these laws have evolved to meet changing social, cultural, and political conditions. It seeks to provide a comprehensive understanding of the principles underl This study offers insights into the dynamics between religious and state laws, providing a clearer perspective on current issues surrounding marriage, such as polygamy and marriage registration. The research is valuable for academics, policymakers, and practitioners, offering practical and theoretical insights into the interplay of Islamic principles and moder.